An analysis of activity nodes and the formulation of a decision support nodal model in the context of the Western Metropolitan Local Council area (greater Johannesburg) - Van der Merwe, Dorothea (Stellenbosch : Stellenbosch University, 2012)
Dissertation (D.Phil.) -- University of Stellenbosch, 1999.